Consumer perceptions of insect meal: An exploratory study in Metropolitan Lima - León Castro, Rocío; Reátegui Ochoa, Piero Alexander; Ledezma Miranda, Clara Iris (LACCEI, 2025)
This study investigated the perceptions of consumers in Metropolitan Lima on the use of insect meal as a sustainable food alternative. Given the need for new sources of protein with low environmental impact, edible insects emerge as a viable option due to their high nutritional value and versatility. 402 people were surveyed using the validated KPEI scale, assessing dimensions such as nutrition, health, sustainability, culture, marketing and social acceptance. The results showed a positive assessment of the nutritional value of insects, although doubts remained about their health safety. Factor analysis confirmed the validity of the instrument and revealed key factors in consumer perception. It is concluded that, despite misinformation and certain cultural barriers, insect meal could be accepted if its nutritional benefits, its low environmental impact and the safe processes by which it is produced are adequately reported, highlighting the importance of consumer education.